A Two-Stage State Feedback Controller Supported by Disturbance-State Observer for Vibration Control of a Flexible-Joint Robot. Issue 6 (19th June 2020) - Pham, Minh-Nha; Hamelin, Philippe; Hazel, Bruce; Liu, Zhaoheng
SUMMARY: Joint flexibility introduces additional degrees of freedom and vibration modes, thus limiting the performance of the manipulator. To improve control bandwidth, this paper proposes an enhanced two-stage state feedback (SFB) controller, which combines two parts. The first is a SFB loop, which considers the motor position as a virtual control input for the link side dynamics. The second is a disturbance-state observer, which compensates disturbances and reconstructs indirect measurements. Experimental results show the effectiveness of the proposed controller in terms of position tracking, link vibration, and rejection of the kinematic error from the joint's harmonic drive reducer.